Immune-Mediated Inflammatory Diseases and Cancer - a dangerous liaison - Maier, Jeanette A.; Castiglioni, Sara; Petrelli, Alessandra; Cannatelli, Rosanna; Ferretti, Francesca; Pellegrino, Greta; Sarzi Puttini, Piercarlo; Fiorina, Paolo; Ardizzone, Sandro (Frontiers in Immunology, 2024)
Patients with Immune-Mediated Inflammatory Diseases (IMIDs) are known to have an elevated risk of developing cancer, but the exact causative factors remain subject to ongoing debate. This narrative review aims to present the available evidence concerning the intricate relationship between these two conditions. Environmental influences and genetic predisposition lead to a dysregulated immune response resulting in chronic inflammation, which is crucial in the pathogenesis of IMIDs and oncogenic processes. Mechanisms such as the inflammatory microenvironment, aberrant intercellular communication due to abnormal cytokine levels, excessive reparative responses, and pathological angiogenesis are involved. The chronic immunosuppression resulting from IMIDs treatments further adds to the complexity of the pathogenic scenario. In conclusion, this review highlights critical gaps in the current literature, suggesting potential avenues for future research. The intricate interplay between IMIDs and cancer necessitates more investigation to deepen our understanding and improve patient management.